2008
DOI: 10.1007/bf03326050
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dissolved oxygen concentration and aeration time on nitrite accumulation in partial nitrification process

Abstract: This study investigated the influence of dissolved oxygen concentration and aeration time on nitrification and nitrite accumulation in an attempt to optimize the recently developed biological-partial-nitritation process for the treatment of strong nitrogen wastewaters. Investigation of dissolved oxygen concentration on ammonium and nitrite oxidation was carried out in a batch reactor. The dissolved oxygen concentration of 0.5 mg O 2 /L inhibited both ammonium as well as nitrite oxidation, while increase of dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…6a, b. These results show that the DO level is a critical operating parameter to optimize in order to achieve efficient nitrogen removal, as also reported in Guo et al (2008).…”
Section: Modelling-nitrogen Fatesupporting
confidence: 81%
“…6a, b. These results show that the DO level is a critical operating parameter to optimize in order to achieve efficient nitrogen removal, as also reported in Guo et al (2008).…”
Section: Modelling-nitrogen Fatesupporting
confidence: 81%
“…The closeness of the ammonianitrogen removal efficiency and the nitrite conversion efficiency indicates that AOB activity improved and NOB was gradually eliminated. In the first few days of the SBR operation, the higher nitrate concentration of the effluent was likely due to the controlled DO range of 0.3-1.0 mg/L (0.65 mg/L on average) [18]. After reducing the DO to 0.2-0.7 mg/L (0.45 mg/L on average) the nitrate concentration in the effluent was reduced to below 5 mg/L.…”
Section: Overview Of the Partial Nitrification Operation Started By Controlling Phmentioning
confidence: 99%
“…Thus, the organic materials were purified and the water quality was improved (Subhasis et al, 1999;Soltanali and Haghani, 2008;Madukasi et al, 2010). Engineering practices also demonstrated that aeration technique was effective to help treating polluted water (Scholz and Lee, 2005;Ouellet-Plamondon et al 2006;Guo et al, 2008;Thakre et al, 2009;Igbinosa and Okoh, 2009). Floating-beds form natural phytodepuration systems and artificially constructed floating-beds are currently used extensively for the purposes of treating domestic, agricultural and industrial effluent (Davies et al 2005;Kovacic et al 2006;Nahlik and Mitsch, 2006;Dhote and Dixit, 2009).…”
Section: Introductionmentioning
confidence: 99%